First report of stem gall in papaya caused by Pantoea dispersa. (14th December 2021) - Ajith, P. M.; Stella Doncy, P. P.; Gautam Ajith, P.; Rajeshkumar, P. P.; Mathew, Deepu; Yamini Varma, C. K.; Deena, S.
Abstract: Callus like galls were observed inside the stem of more than 5-year old papaya trees in Kerala, India. The bacterium Pantoea dispersa and the fungus Fusarium spinosum were isolated from these galls. Identity of the fungus was confirmed by sequencing and analysis of rDNA region, EFα gene and phylogenetic and barcode analyses. Bacterial identity was confirmed by analysis of rDNA region. Pathogenicity tests with a combination of the fungus and bacterium and bacterium alone, resulted in gall formation. Individual inoculation of F. spinosum did not result in gall. Only P. dispersa was re-isolated from the galls, indicating its etiological role. Supplemental data for this article is available online at https://doi.org/10.1080/03235408.2021.1974686 .